Correlation analysis between jejunum metabolites and immune function in Saba and Landrace piglets - He, Yang; Li, Yongxiang; Pan, Yangsu; Li, Anjian; Huang, Ying; Mi, Qianhui; Zhao, Sumei; Zhang, Chunyong; Ran, Jinming; Hu, Hong; Pan, Hongbin (Frontiers in Veterinary Science, 2023)
The immune function of the intestinal mucosa plays a crucial role in the intestinal health of hosts. As signaling molecules and precursors of metabolic reactions, intestinal chyme metabolites are instrumental in maintaining host immune homeostasis. Saba (SB) pigs, a unique local pig species in central Yunnan Province, China. However, research on jejunal metabolites in this species is limited. Here, we used immunohistochemistry and untargeted metabolomics by liquid chromatography mass spectrometry (LC-MS/MS) to study differences in jejunal immunophenotypes and metabolites between six Landrace (LA) and six SB piglets (35 days old). The results showed that the levels of the anti-inflammatory factor interleukin 10 (IL-10) were markedly higher in SB piglets than in LA piglets (P < 0.01), while the levels of the proinflammatory factors IL-6, IL-1β, and Toll-like receptor 2 (TLR-2) were markedly lower (P < 0.01). Furthermore, the levels of mucin 2 (MUC2) and zona occludens (ZO-1), which are related to mucosal barrier function, were significantly higher in SB piglets than in LA piglets (P < 0.01), as were villus height, villus height/crypt depth ratio, and goblet cell number (P < 0.05). Differences in jejunal chyme metabolic patterns were observed between the two piglets. In the negative ion mode, cholic acid metabolites ranked in the top 20 and represented 25% of the total. Taurodeoxycholic acid (TDCA) content was significantly higher in SB piglets than in LA piglets (P < 0.01). TDCA positively correlated with ZO-1, villus height, villus height/crypt depth ratio, and goblet cell number. These results suggest that SB pigs have a strong jejunal immune function and that TDCA was positively regulates jejunal immunity and mucosal barrier function. Our findings provide a reference for understanding intestinal immune function in different pig breeds and for the discovery of potential biomarkers to help solve health issues related to pig production.